THE EFFECT OF SOCIAL MEDIA MARKETING AND BRAND AWARENESS ON PURCHASE INTENTION WITH FOMO AS A MEDIATING VARIABLE: A STUDY OF ADIDAS SAMBA PRODUCTS - Khairunnisaa Khairunnisaa; Roslina Roslina; Yuniarti Fihartini (Journal of Economic, Bussines and Accounting (COSTING), 2026)
The purpose of this study is to examine the influence of social media marketing and brand awareness on purchase intention, with Fear of Missing Out (FoMO) as a mediating variable, among consumers of Adidas Samba products. This study employs a quantitative approach using purposive sampling. 260 respondents were selected based on the criteria of having knowledge about Adidas Samba product information obtained through social media and being aware of Adidas Samba as part of the Adidas brand. Data analysis was conducted using SEM-PLS. The results found that social media marketing and brand awareness have a positive and significant influence on purchase intention, brand awareness has a positive and significant influence on FoMO, whereas social media marketing has no significant influence on FoMO. FoMO was found to have a positive and significant influence on purchase intention. The mediation test results showed that FoMO does not mediate the effect of social media marketing on purchase intention but is able to positively and significantly mediate the relationship between brand awareness and purchase intention.